Peningkatan Pengetahuan Pernikahan Dini Pada Siswa SMP Negeri 2 Cina Kabupaten Bone - Musni, Musni; Fatmasanti, Ulfa; Syam, Azniah (UKInstitute, 2022)
The Covid-19 pandemic not only has an impact on health and economic problems but also has an impact on increasing early marriage. Early marriage is a marriage that is not allowed because it violates the age limit for marriage, the provisions of which must be married at the age of more than 19 years but carried out when the age is under 19 years. The issue of early marriage has become a separate problem for Indonesia. There are many facts behind underage marriage. Some of them are as a solution to the family economy, the influence of local religious and cultural norms, and the lack of education related to early marriage. Early marriage can cause teenagers to drop out of school, reproductive health problems, low birth weight babies, psychological disorders and increase divorce rates. Community service activities are carried out to increase students' knowledge about the impact of early marriage. Community service activities are carried out using the lecture method (counseling). Before and after the counseling students were given pre-test and post-test questionnaires. The results of community service activities, namely before counseling students with good knowledge categories were 30% and after counseling increased to 78%, this indicates an increase in student knowledge after counseling about the impact of early marriage in SMP Negeri 2 Cina